Preliminary study analysis on magnetic field exposure assessment in Selangor public schools - Hashim J.; Farag A.S.; Hussain H.; Said I.; Rahman N. (2023)
Exposure assessment is the determination or estimate of the magnitude, frequency of occurrence and rate of exposure of an individual or a group to an environmental agent [3]. Electromagnetic field (EMF) health issue has been traced to be developed for the past 30 years and scores of studies have been carried out to Und the relationship between EMF and health problems. However, scientists are still far from making a conclusion on whether EMF does pose health hazards. The study carried out in 4 primary schools and 1 secondary school in Selangor is the preliminary study to measure the level of magnetic field school children are exposed daily when attending school. Magnetic field data collection was carried out in order to determine the level of magnetic field in both the indoor and outdoor areas of each school selected. In order to determine and compare the distribution of average magnetic fields in the 5 different schools, analysis that has been done using statistical software is presented in the form of tables and plots and will be discussed briefly. 2005 IEEE.